Edukasi Latihan Core untuk Mengatasi Nyeri Pinggang Bawah (Low Back Pain) pada Anggota Dharma Wanita Persatuan Balai Perikanan Budidaya Laut (BPBL) Ambon Tahun 2024 - Yulianti Ely (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Lower back pain is pain in the lower back area that is felt down to the buttocks and thighs which is often found in society, especially in housewives. The core is the central part of the body including the pelvis, lower back and hips. Core exercises train the muscles to work in harmony and improve body balance. This study uses leaflet media and direct tutorials to members of the Dharma Wanita Persatuan Balai Perikanan Budidaya Laut (BPBL) Ambon to overcome lower back pain (Low Back Pain).